ANALISIS GREEN BRAND IMAGE, GREEN PRODUCT DAN GREEN ADVERTISING TERHADAP ECO-FRIENDLY PRODUCT PURCHASE DECISION - Adhitya Yoga Prasetya; Arona Jaya Telaumbanua; Sari Rahmadhani (Universitas Sains dan Teknologi Komputer, 2019)
. The purpose of this study is to Analysis affecting Green Brand Image, Green Product and Green Advertising on Eco-Friendly Product Purchase Decision. The independent variables analyzed in this study are Green Brand Image, Green Product, Green Advertising and Eco-friendly Product Purchase Decision as the dependent variable. The sample used in this study consisted of 100 Green Wash Users. Sampling was done by purposive sampling method by distributing questionnaires. Analysis in this research uses a test of validity and reliability, a test of classical assumptions, a test of statistical assumptions, a test of normality, a multicollinearity test, a heteroscedesticity test, a multiple linear regression test, a feasibility test of capital (F test) of the test of the significance of individual parameters (statistical test t) and a test of coefficient of determination. (R2) with the help of the SPSS program. The results showed that the Green Brand Image had a positive and significant effect, the Green Product had a positive and significant effect, the Green Brand Image had a positive and significant effect on the Eco-friendly Product Purchase Decision.